Profile of physical demands in female soccer players during competitions: A systematic review - Rodríguez Porras, L. D.; Solano-Mora, L.; Rivas-Borbón, M.; Moreno-Villanueva, A.; Soler-López, A.; Pino-Ortega, J.; Ugalde-Ramírez, J. A. (Strength and Conditioning Journal, 2024)
The rapid expansion of women's soccer has triggered scientific curiosity to gain a deeper understanding of its game dynamics. To organize scientific findings related to the physical demands of women's soccer during official competitions, contextual factors such as game positions, match periods, type of competition, and match outcomes have been considered. This aims to provide a comprehensive and current overview of physical exertion profiles. This systematic review included PubMed, Scopus, SPORTDiscus, Web of Science, Science Direct, ERIC, and Scielo electronic databases. A total of 1,859 studies were found, of which, after meeting the inclusion and exclusion criteria, 28 articles were selected. The study found high variability in racing thresholds for high speeds, with central midfielders covering more total distance and wingers covering more distance at high intensities. Forwards register more sprints, and physical efforts decrease in the second period of the game. International matches demand more effort, and physical demands in women's soccer are influenced by contextual factors. To design effective training programs, specific profiles for each game position and the type of competition should be considered, and standardization of high intensity and acceleration thresholds is necessary for accurate conclusions.